Carcinoma de células de Merkel - A propósito de um caso clínico - Moura Alves, A. M.; Gomes, Guilherme; Araújo, Rosário; Pereira, Carmen; Rodrigues Dias, A. (Portuguese Journal Internal Medicine, 1995)
In the present work the authors make a presentantion of a clinical case relative to a woman of 80 years old, admitted in Internal Medicine Service grounds, by a question of lymph node metastasis of unknown primary carcinoma, that resulted in a diagnosis of 'Merkel Cell Carcinoma'. The case, taken on account its relative rarity, motivated a comprehensive review about the origin, pathoenesis, clinical behaviour and therapeutic solutions.